The Importance of the Roles of Parents and Teachers in Cultivating Honesty in Early Childhood Characters - Febriani, Hani; Anesty Mashudi, Esya; Tewari, Vena (Indonesian Journal of Early Childhood Educational Research (IJECER), 2023)
The purpose of this research is to describe that the importance of the role of parents and teachers in shaping children's honest character because the role of educating children is not only from one direction but from many directions that are interrelated not contradictory. This research method is a library research with a qualitative approach where all data is obtained from the analysis of various previous studies related to the topic discussed. The results showed that it is very important to collaborate between the role of parents and teachers in shaping children's honest character, because in instilling character values to children it must be done by habituation. Where this habituation does not apply only at home or at school. This habituation is carried out at home with the role of parents and at school with the role of teachers.┬á┬á